2006
DOI: 10.3168/jds.s0022-0302(06)72216-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Proteins in Bovine Milk in an Experimental Model of Staphylococcus aureus Subclinical Mastitis

Abstract: The objectives were to establish the origin of 2 acute phase proteins in milk during subclinical bovine mastitis and to characterize the relationship between those proteins in milk and blood. Haptoglobin (Hp) and mammary-associated serum amyloid A (M-SAA3) appear in milk during mastitis, whereas Hp and serum amyloid A increase in serum during mastitis. The concentrations of these proteins were determined in an experimental model using a field strain of Staphylococcus aureus to induce subclinical mastitis in da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
122
6
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 41 publications
16
122
6
2
Order By: Relevance
“…However, in both studies, SAA but not Hp was also detected in some control quarter samples. Likewise, in a study on experimental subclinical mastitis (Eckersall et al 2006) the authors found SAA in some of the control quarters. During certain physiological conditions, such as at dry-off and oestrus, the permeability of the blood/milk barrier is increased resulting in leakage of blood proteins into milk.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, in both studies, SAA but not Hp was also detected in some control quarter samples. Likewise, in a study on experimental subclinical mastitis (Eckersall et al 2006) the authors found SAA in some of the control quarters. During certain physiological conditions, such as at dry-off and oestrus, the permeability of the blood/milk barrier is increased resulting in leakage of blood proteins into milk.…”
Section: Discussionmentioning
confidence: 87%
“…Some studies also relate to milk from clinically healthy cows (Eckersall et al 2001 ;Grö nlund et al 2003 ;Nielsen et al 2004 ;Grö nlund et al 2005;Lindmark-Månsson et al 2005;Eckersall et al 2006;O'Mahony et al 2006), while only a few studies relate to milk from subclinical mastitis (Grö nlund et al 2005;Eckersall et al 2006;O'Mahony et al 2006). Eckersall et al (2001) compared the concentrations of Hp and SAA in milk from clinically healthy dairy cows and from cows with clinical mastitis of varying severity.…”
mentioning
confidence: 99%
“…In studies of bovine respiratory disease, peak levels of serum SAA and HPT were reported during week 3 of an outbreak of respiratory disease in calves caused by respiratory syncytial virus (Orro et al, 2011), while experimental infection with respiratory syncytial virus caused maximal increases in serum levels of HPT and SAA in cattle as early as 7-8 days following inoculation (Heegaard et al 2000). Of the bovine diseases studied, however, APP expression has been investigated most extensively during mastitis in lactating dairy animals (Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2006Eckersall et al, , 2001Grönlund et al, 2003;Hirvonen et al, 1999). Mastitis is defined as an inflammation of the mammary gland, and is considered the most dominant and costly of diseases to affect lactating dairy cattle.…”
Section: Modulation Of Acute Phase Proteins During Ruminant Diseasementioning
confidence: 99%
“…Veterinary Biomarker Discovery: Proteomic Analysis of Acute Phase Proteins 191 2.1 Modulation of acute phase proteins during disease in swine Alteration in APP expression has been associated with a number of food animal diseases (Table 1), including mastitis, metritis, and amyloidosis in lactating dairy cattle (Chan et al, 2010;Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2001Eckersall et al, , 2006Takahashi et al, 2006;Grönlund et al, 2003Grönlund et al, , 2005; sepsis, trauma, and respiratory diseases in swine (Amory et al, 2007;Sorensen et al, 2006;Hultén et al, 2003;Heegaard et al, 1998;Eckersall et al, 1996); infectious bronchitis virus in chickens (Nazifi et al, 2011); respiratory diseases in beef cattle (Orro et al, 2011;Heegaard et al, 2000;Godson et al, 1996;Horadagoda et al, 1995); as well as pulmonary damage and caseous lymphadenitis in sheep (Eckersall et al, 2007;Pfeffer and Rogers, 1989 In swine, increased levels of serum HPT have been associated with pathological indications of Mycoplasma hyopneumoniae, a leading cause of porcine enzootic pneumonia (Amory et al, 2007). Similarly, serum concentrations of HPT and SAA were elevated in pigs with experimentally induced Actinobacillus pleuropneumoniae pneumonia Heegaard et al, 1998).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation